1984
DOI: 10.1111/j.1365-2559.1984.tb02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunopathologic study of mesangial IgM nephropathy: report of 41 cases

Abstract: Forty-one out of 408 cases (or 10%) of primary glomerular disease had diffuse fine granular to arc-like short linear mesangial deposits of IgM by direct immunofluorescence. The IgM deposition was accompanied by C1q and/or C4 in the same locality in 29 cases, by C3 in 10, and by trace amounts of IgA in 6. Properdin-factor B was not detected. Fine granular electron dense deposits of low density were detected in the mesangium in all 41 cases by electron microscopy, usually as a discrete granular or arc-like patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0
4

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 10 publications
6
69
0
4
Order By: Relevance
“…We found that the patients with IgM deposition presented with higher levels of serum IgM. This is consistent with the observations in IgM nephrology (23,24). These data implied that the glomerular IgM deposits are composed of specific clones of IgM, possibly from B-1a B cells (3,25,26), which are produced in circulation and bind to some epitopes on sclerotic segments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the patients with IgM deposition presented with higher levels of serum IgM. This is consistent with the observations in IgM nephrology (23,24). These data implied that the glomerular IgM deposits are composed of specific clones of IgM, possibly from B-1a B cells (3,25,26), which are produced in circulation and bind to some epitopes on sclerotic segments.…”
Section: Discussionsupporting
confidence: 92%
“…The pathologic variants and percentage of sclerotic glomeruli were also comparable between the two groups. These findings indicated that IgM deposition is not likely the initiation of FSGS lesion, which has been identified as several genes mutations or variants (9-13), circulating permeability factors (14)(15)(16), and others (17)(18)(19)(20)(21)(22)(23). However, IgM and complement-mediated injury may be secondary phenomena that occur after the primary renal insult.…”
Section: Discussionmentioning
confidence: 97%
“…6 Importantly, C3 and C4 are frequently detected in the glomeruli of patients who have IgM deposits. 4,7,8 In spite of its promiscuous presence in glomerular lesions, a pathogenic role for glomerular IgM has not been demonstrated. Some series, however, have shown that the presence of IgM is of prognostic significance.…”
mentioning
confidence: 99%
“…However, many of us regard it as a distinct histological entity with different response to steroid, requiring immunosuppressant therapy. [6][7][8][9][10][11] We believe that IgM nephropathy remains a separate histological entity with steroid responsiveness, course, and prognosis far different from MCD. About 23.5% of our cases showed renal insufficiency with a serum creatinine varying from 1.4 to 5 mg%.…”
Section: Discussionmentioning
confidence: 99%